Leucism in the marbled swamp eel Synbranchus marmoratus Bloch, 1795 (Synbranchiformes: Synbranchidae) - Paschoal, Lucas Rezende Penido [UNESP]; Zara, Fernando José [UNESP]; Borges, Lucas Elias Oliveira; Azevedo-Santos, Valter M. (FapUNIFESP (SciELO), 2024)
Leucism is an anomaly recorded in fish species as well as in many other groups of animals in natural environments. An individual with leucism is characterized by the loss of brown or black pigmentation over most of the body. Here, we recorded this condition for an individual of marbled swamp eel Synbranchus marmoratus (Synbranchiformes: Synbranchidae) captured in the Furnas megareservoir, Grande River basin, in Minas Gerais state, southeastern Brazil. The individual had a general color of the body with shades ranging from pale to intense yellowish, but the eyes were black. We also present a discussion on the influence of leucism on the survival of the individual in this study.
Leucismo em muçum Synbranchus marmoratus Bloch, 1795 (Synbranchiformes: Synbranchidae)
Keywords: Color anomaly; fish; Furnas megareservoir; Grande River basin; pigmentation